Materiały krzemienne z późnomezolitycznego stanowiska Jastrzębia Góra 4, województwo gdańskie - Ruta, Sławomira (Acta Universitatis Lodziensis. Folia Archaeologica, 1997)
The paper is mostly devoted to Dint working technique in the inventory from Jastrzębia Góra. The site lying on the north-west edge of the Kępa Swarzewska was found in 1972 by W. Chmielewski. In years 1975-1977 and 1980 it was being explored by L. Domańska. A collection of four thousand flints was gathered. At first it had been assigned to the Chojnice-Pieńki culture but recently to the post-Maglemose. The material was arranged in two main concentrations of similar features. Two techniques of tool production (splinter and blade ones) were recognized in the inventory. Splinter cores dominate here (c. 90% of cores). Blade ones are small, microlithic, conical and sub-conical. The inventory has some characteristic features. Technical operations connected with prepairing and repairing blade cores were reduced to minimum. Splinter and blade techniques intermingle with each other. Blades are very regular and slim and they were used as inserts (without retouch) or for producing microliths. A great importance of the technique of obtaining blade semi-products is evident. The rest of tools were made mostly from splinter semi-products and side-scrapers dominate here. The Pomeranian flint is almost the only one (99%) that was used in Jastrzębia Góra, site 4 therefore the techniques distinguished there are determined by that stone material.